Evaluasi Usability Dan Perbaikan Antarmuka Pengguna Pada Aplikasi E-Suket Kota Kediri Menggunakan Metode Usability Testing - Ihsa Almasyah Pahlevi; Retno Indah Rokhmawati; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
E-Suket of Kediri City is an android-based application for independent official letter services for resident of Kediri City. Based on the result of a study of user reviews on the Google Play Store, there are several problems that users found while using the application, including failing to submit letter request and errors. Therefore, important to evaluate and improving the E-Suket application so it can increase it usability value. The evaluation method used is usability testing, which in the testing process involves the users to assess the extent to which the application has met the criteria being tested. Evaluation is done by testing assignments, filling out questionnaires, and interviews. In the evaluation process, the aspects being measured is based on ISO 9421-11 which are effectiveness, efficiency, and user satisfaction. Testing was done twice, namely testing on the initial design of application and testing on the recommendations for design improvement made based on the results of the initial design evaluation analysis. Based on the results of interviews with test respondents, there were 27 problems found in the application. There are 28 guidelines for developing recommendations for application design improvements. The test results on effectiveness aspect shows 55,5% for the initial design and 100% for the design recommendation, the test results on the effectiveness aspect shows 54,42% for the initial design and 100% for the design recommendation, and the test results on users satisfaction aspect using the SUS questionnaires shows 43,75 for initial design and 66,5 for design recommendation.